Lagrangian Studies of Net Community Production: The Effect of Diel and Multiday Nonsteady State Factors and Vertical Fluxes on O2/Ar in a Dynamic Upwelling Region. Issue 6 (4th June 2020) - Wang, Seaver; Kranz, Sven A.; Kelly, Thomas B.; Song, Hajoon; Stukel, Michael R.; Cassar, Nicolas
Abstract: The ratio of dissolved oxygen to argon in seawater is frequently employed to estimate rates of net community production (NCP) in the oceanic mixed layer. The in situ O2 /Ar‐based method accounts for many physical factors that influence oxygen concentrations, permitting isolation of the biological oxygen signal produced by the balance of photosynthesis and respiration. However, this technique traditionally relies upon several assumptions when calculating the mixed‐layer O2 /Ar budget, most notably the absence of vertical fluxes of O2 /Ar and the principle that the air‐sea gas exchange of biological oxygen closely approximates net productivity rates. Employing a Lagrangian study design and leveraging data outputs from a regional physical oceanographic model, we conducted in situ measurements of O2 /Ar in the California Current Ecosystem in spring 2016 and summer 2017 to evaluate these assumptions within a "worst‐case" field environment. Quantifying vertical fluxes, incorporating nonsteady state changes in O2 /Ar, and comparing NCP estimates evaluated over several day versus longer timescales, we find differences in NCP metrics calculated over different time intervals to be considerable, also observing significant potential effects from vertical fluxes, particularly advection. Additionally, we observe strong diel variability in O2 /Ar and NCP rates at multiple stations. Our results reemphasize the importance of accounting for vertical fluxes when interpreting O2 /Ar‐derived NCP data and the potentially large effect of nonsteady state conditions on NCP evaluated over shorter timescales. In addition, diel cycles in surface O2 /Ar can also bias interpretation of NCP data based on local productivity and the time of day when measurements were made. Plain Language Summary: Marine microbes produce and consume oxygen as a product of a balance between photosynthesis and respiration, thereby causing changes in the concentration of oxygen in the surface ocean. Taking advantage of known relationships between the gas properties of oxygen and argon, researchers can isolate changes in biologically produced oxygen from changes that result from physical processes. This calculation relies on several simplifying assumptions. In this study, we test the importance of these assumptions by tracking changes in biological oxygen while following several water parcels over the course of 2–4 days. We find that accounting for vertical mixing processes and the rate of change in biological oxygen is important when estimating biological oxygen production rates. We also find that daily shifts in oxygen as photosynthesis rises through the day and falls to zero at night can influence measurements based on time of collection. Key Points: We employ Lagrangian observations of O2 /Ar in the California Current to test assumptions inherent to the O2 /Ar‐based NCP method We demonstrate the significance of vertical fluxes and diel patterns in O2 /Ar that can bias NCP measurements Nonsteady state conditions and vertical fluxes strongly complicate efforts to evaluate O2 /Ar‐based NCP on short timescales